Analysis of the Factors Affecting the Development of Economic Culture of a Family in the Russian Federation Based on Experience of Developed Countries - Nosova, Svetlana Sergeevna; Abdulov, Rafael Envarovich; Medvedeva, Yulia Mihailovna (International Review of Management and Marketing, 2016)
The article discusses the issues related to the possibility of using foreign experience in the system of economic culture formation in the family. The author considers factors that can serve a catalyst in the policy formation as pertaining to economic culture of the family, analyzing economic culture formation of the families in developed countries and proposing characteristic of the family economic culture concept. The author discusses the possibility of considering this concept within the framework of a separate category, different from the concepts of economic culture of the individual and economic culture of the society. A multilevel system to form economic culture of the family, involving secondary and higher levels of education into this process, is considered. The author analyzes the basic assumptions developed to create a new avenue in social policy of the state in the field of economic knowledge popularization. Keywords: family, education, economic culture, development. JEL Classifications: D83, Z13